Analisis Semiotika Kekerasan dalam Film Drama Korea The Penthouse: War In Life I - Safira, Ratih (Communication & Social Media, 2022)
Analysis of Semiotics of Violence in the Korean Drama Film The Penthouse: War In Life Season 1 (Representation of Violence Scenes in Impressions of 15 Years of Age)" is the title of this study. This study aims to examine how The Penthouse: War In Life Season 1 of the Korean drama film The Penthouse depicts violence in the fifteen-year-old program. Representation theory and semiotic theory were employed by the author to analyze this research. The scene from The Penthouse: War in Life Season 1 of the Korean drama film serves as the subject of this study. The approach is a qualitative descriptive approach. With Charles Sanders Pierce's model's semiotic analysis technique, which employs the idea of triangle meaning, namely: sign (sign), sign reference (object), and use of sign (interpretant). The findings of this study can be seen in the way that the Korean drama film The Penthouse: War In Life Season 1 depicts symbols, items, and interpreters that are synonymous with violence. starting with murder, abuse of others' rights, bullying, and psychological violence.